Influence of the heated blocks on the natural convection in 3D cylindrical and divergent annular duct. (2017) - Benkherbache, Souad; Si-Ameur, Mohamed
In this paper, a numerical investigation of natural convection in three-dimensional cylindrical and divergent annular duct is studied. In the inner cylinder of thin thickness, are mounted a cylindrical blocks which subjected to a volumetric heat generation. The governing equations of mass, momentum and energy equation for both the fluid and the solid are solved by the finite volume method using the commercially available CFD software Fluent. The effect of the number of heated blocks (N = 1, 2, 3 and 5) and the inclination angle of the divergent (φ = 0°, 15°, 23° and 45°) have been studied. The temperature and velocity contours fields, stream lines also the local Nusselt number have been presented here for Ra = 2.10 5 and N = 3 while temperature and velocity profiles in the span-wise direction of the flow were plotted for Ra = 1.105 (φ = 0°, 15°, 23° and 45°) and (N = 1, 2, 3 and 5) also the local and average Nusselt number for those geometries.